Dynamics of prostaglandin E2 in the surgical treatment of gastroesophageal reflux disease - Ye. I. Haidarzhi (Patologìâ)
Gastroesophageal reflux disease (GERD) is one of the most common gastroenterological diseases. Therefore, the issues of diagnosis and the most effective treatment of GERD are extremely relevant. Achieving a stable positive result of treatment is impossible without taking into account the pathogenetic mechanisms of the development of GERD. Particularly relevant are the little-studied issues of the influence of humoral factors on the development of GERD in the course of treatment. One of the interesting biologically active substances is prostaglandin E2, the possible involvement of which in the mechanisms of the development of GERD is insufficiently reported.